2002
DOI: 10.1081/jas-120015798
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Knowledge and Medication Compliance Among Parents of Asthmatic Children in Nanjing, China

Abstract: Asthma knowledge and medication compliance among parents of 150 asthmatic children in Nanjing were assessed using a self-administered questionnaire. The results showed that 54.7% of parents had poor knowledge of asthma and its management. Parental compliance with medication was also suboptimal as only 43.3% of parents reported adherence with prescribed anti-asthmatic medication for their children. Reasons for non-compliance included fear of medication side-effects and tolerance, and forgetting to give the chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
0
19
2
Order By: Relevance
“…Similarly, a study in China reported that 63.3% of parents knew that asthma is due to inflammation and swelling of the lungs [15]. A systematic review of factors affecting adherence to asthma treatment by Howel [26] showed that a poor understanding of the role of controller medications is significantly associated with a lack of adherence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, a study in China reported that 63.3% of parents knew that asthma is due to inflammation and swelling of the lungs [15]. A systematic review of factors affecting adherence to asthma treatment by Howel [26] showed that a poor understanding of the role of controller medications is significantly associated with a lack of adherence.…”
Section: Discussionmentioning
confidence: 98%
“…Various aspects of knowledge related to asthma management, such as poor understanding of the nature of the disease, parental myths and beliefs and a lack of knowledge about main triggers, asthma treatment and medications, have been explored in previous studies [14][15][16][17][18]. Unfortunately, we were not able to identify similar studies conducted in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 87%
“…The presence of higher FeNO levels indicated the existence of airway inflammation, even in a relatively "healthy" status. Actually, there is a relatively lower prevalence of chronic steroid application in children with asthma in China, and a survey performed in a large children's hospital showed that only 43.3% of parents reported adherence to prescribed anti-asthma medications for their children (26). High airway inflammation could be a risk factor for subsequent asthma relapse (27); this indicated that it is important to control airway inflammation in the asthmatic patients even without clinical symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…. " (19). Some, however, were quick to point out that the amount of responsibility given to a child needed to be individualized and developmentally appropriate.…”
Section: Shifts In Responsibilitymentioning
confidence: 94%
“…Children may not be motivated to adhere to regimens (16) and may therefore need reminding by parents (17). Previous research has identified a strong parental fear of side effects from asthma medicines, particularly from corticosteroids (18,19). Child embarrassment over taking medicines in public has also been reported (16).…”
Section: Introductionmentioning
confidence: 95%